Mobile Phone Ecological Momentary Assessment of Daily Stressors Among People Living With HIV: Elucidating Factors Underlying Health‐Related Challenges in Daily Routines. (September 2017) - Farmer, Shu; Mindry, Deborah; Comulada, Scott W.; Swendeman, Dallas
Abstract : N/A: Stressful life events and daily hassles affect people living with HIV (PLWH). However, capturing stress‐related events and cognitive impairment is often plagued with recall biases. Incorporating reliable information technology, such as mobile phones, can be a resourceful method for measuring health behaviors (MHB). We report findings from an MHB pilot study with 32 African American, Latino/Hispanic, and White PLWH from Los Angeles. Participants reported perceived stressors in their daily routines using a smartphone Ecological Momentary Assessment (EMA) application. Participants self‐initiated in‐the‐moment stressful events reports for up to 6 weeks. Stressful event EMAs queried perceived stress levels (1–10 scale) and open‐ended text descriptions. Qualitative analysis of participant text responses was completed using grounded thematic coding. Participants reported multiple stressors in their daily routines, impacting activities of daily living or daily functioning. Eliciting input from PLWH via EMA in real time is a novel approach for assessing and identifying sources of stress.